Pengaruh Marketing Mix Terhadap Keputusan Pembelian Sepeda Motor Di Dealer “Trijaya Motor” Surakarta - Hartati Dyah Wahyuningsih - STMIK AUB Surakarta (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2017)
Abstract - Indonesia's economic development in the country, especially in the motorcycle trade industry is now very rapidly and attracted the attention of researchers to conduct research, particularly in purchasing decisions motorcycle Dealer